2004
DOI: 10.1074/jbc.m406966200
|View full text |Cite
|
Sign up to set email alerts
|

TDAG8 Is a Proton-sensing and Psychosine-sensitive G-protein-coupled Receptor

Abstract: T cell death-associated gene 8 (TDAG8) has been reported to be a receptor for psychosine. Ovarian cancer G-protein-coupled receptor 1 (OGR1) and GPR4, Gprotein-coupled receptors (GPCRs) closely related to TDAG8, however, have recently been identified as protonsensing or extracellular pH-responsive GPCRs that stimulate inositol phosphate and cAMP production, respectively. In the present study, we examined whether TDAG8 senses extracellular pH change. In the several cell types that were transfected with TDAG8 cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
226
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(250 citation statements)
references
References 19 publications
22
226
2
Order By: Relevance
“…Under the present assay conditions, we observed no effect of psychosine on TDAG8. The differences in the cAMP assay method, parental cell lines, and sublines, or intracellular localization of the expressed receptor may explain the discrepancy between our results and the previous reports (3,34). In addition, high concentrations of psychosine have been reported to possess a detergent-like hemolytic activity in vitro (35).…”
Section: Cd8contrasting
confidence: 57%
See 2 more Smart Citations
“…Under the present assay conditions, we observed no effect of psychosine on TDAG8. The differences in the cAMP assay method, parental cell lines, and sublines, or intracellular localization of the expressed receptor may explain the discrepancy between our results and the previous reports (3,34). In addition, high concentrations of psychosine have been reported to possess a detergent-like hemolytic activity in vitro (35).…”
Section: Cd8contrasting
confidence: 57%
“…In addition, high concentrations of psychosine have been reported to possess a detergent-like hemolytic activity in vitro (35). Concerning calcium mobilization, Wang et al (34) and also we were unable to see the stimulatory effect of psychosine, whereas Im et al response. Further studies are needed to explain these differences and to determine whether or not TDAG8 works as a proton sensor in vivo.…”
Section: Cd8contrasting
confidence: 44%
See 1 more Smart Citation
“…As previously reported, 17 Intriguingly, recent studies demonstrated that G2A, as well as 3 related GPCRs-OGR1, GPR4, and TDAG8-can sense pH change to elicit downstream biologic activities such as inositol phosphate (IP) and cAMP formation. [40][41][42] LPC functions like an antagonist to decrease the pH-dependent activation of G2A in the IP assay. 41 A histidine (H174) in the human receptor plays a role in the proton-sensing function of G2A.…”
Section: Org Frommentioning
confidence: 99%
“…The original observations related to the ability of these receptors to recognize protons were conducted in osteosarcoma cells and primary human osteoblast precursors and showed that acidosis triggered inositol phosphate formation (28). Subsequent studies performed in a variety of transfected cell lines cultured at low values of extracellular pH (6.0 -7.0), found that OGR1 and G2A lead to the accumulation of inositolphosphate, whereas GPR4 and TDAG8 elicit cAMP formation (29,30). The expression and function of these receptors in human leukocytes has not been defined.…”
mentioning
confidence: 99%